Hepatoprotective and Antiatherosclerotic Effects of Oleoylethanolamide-Based Dietary Supplement in Dietary-Induced Obesity in Mice - Darya Ivashkevich; Arina Ponomarenko; Igor Manzhulo; Anastasia Egoraeva; Inessa Dyuizen (Pathophysiology, 2025)
Background: Metabolic effects of oleoylethanolamide-based dietary supplement (OEA-DS) were studied in a model of dietary-induced obesity in mice. Obesity was induced by a 2-month high-fat, high-cholesterol diet, resulting in significant morphological changes in liver tissues and elevated cholesterol levels in the animals’ blood serum. Elevated levels of proinflammatory cytokines, oxidative stress, and hepatocyte apoptosis were also observed in the liver tissue. The aim of this study was to examine the mechanisms through which an OEA-based dietary supplement (OEA-DS) exerts a comprehensive influence on multiple aspects of the pathogenesis of MASLD, thereby demonstrating a robust hepatoprotective effect. Methods: mice were fed a high-fat, high-cholesterol diet with or without OEA-DS supplementation. Liver tissues and blood serum were analyzed for cholesterol levels, inflammatory markers (CD68, Iba-1, CD163, IL-1β, IL-6, TNFα), apoptotic markers (Bad, Bax, Bcl-2), nuclear receptors (PPAR-α, PPAR-γ, AdipoR1), and enzymes involved in lipolysis (Acox1, Cpt1a) and cholesterol metabolism (Ldlr, Furin, Pcsk9). Immunohistochemistry, Western blotting, and RT-PCR were used to assess protein expression and gene transcription. Results: administration of OEA-DS normalized cholesterol levels, decreased expression of inflammatory markers (CD68 and Iba-1), pro-apoptotic markers (Bad, Bax) and levels of pro-inflammatory cytokines (IL-1β, IL-6, TNFα). In parallel, the expression of nuclear receptors PPAR-α and PPAR-γ, adiponectin receptor 1 (AdipoR1), and anti-inflammatory (CD163) and anti-apoptotic (Bcl-2) markers have risen. OEA-DS administration induced the expression of liver lipolysis enzymes (Acox1, Cpt1a) and cholesterol metabolism factors (Ldlr, Furin), while simultaneously reducing the transcription of the proatherogenic factor Pcsk9. Conclusions: The results of this study suggest a complex action of OEA-DS in obesity-associated liver damage, which includes reduction of systemic inflammation.